PENGARUH METODE PEMBELAJARAN TUTOR SEBAYA TERHADAP MOTIVASI BELAJAR, MINAT BELAJAR DAN HASIL BELAJAR MATEMATIKA KELAS XI ILMU ALAM MAN MODEL SORONG - Pangerti, Budi (Jurnal Ilmu Pendidikan Indonesia, 2015)
This study aims to Know (1) The effect of peer tutoring learning methods on motivation to learn in Class XI Mathematics Natural Sciences MAN Model Sorong. (2) The effect of the method of peer tutoring to learning interest in math class XI Natural Sciences MAN Model Sorong City (3) The influence of peer tutoring learning method to learning outcomes in math class XI Natural Sciences MAN Model Sorong. This study consists of four variables which consists of one independent variable and the dependent variable 3. The results showed that: (1) peer tutoring learning method has significant influence on the motivation to learn ssiwa in math class XI Natural Sciences MAN Model Sorong City 2013-2014 school year. It can be seen from the results of the regression analysis showed that (F count = 159.651)> (F table = 4.17) or the value of sig 0.0000 (F table = 4.17) or the value of sig 0.0000 (F table = 4.17) or the value of sig 0.026